SURVEI KONDISI DAYA TAHAN DAN KEKUATAN FISIK PADA SISWA PUTRA EKSTRAKULIKULER SEPAK BOLA DI SDN II SRATUREJO KECAMATAN SUMBEREJO KABUPATEN BOJONEGORO - Muzakhthafi Fadhli, Moh. Rindam; Roesdiyanto, Roesdiyanto (Sindoro: Cendikia Pendidikan, 2025)
This study aims to determine the level of endurance and physical strength among male students in the football extracurricular program at SDN II Sraturejo, Baureno District, Bojonegoro Regency, aged 10-12 years.The results of this study can be used by PJOK teachers as evaluation materials and benchmarks for training in the learning process.This study has a sample of 15 students.The data collection technique is descriptive quantitative using the survey method.This study obtained results on the arm muscle endurance component (Flexed Arm Hang Test) with an average score of 13.06, achieving a percentage of 46.6% in the sufficient category, on the abdominal muscle strength component (30-Second Sit-up Test) with an average score of 16, achieving a percentage of 46.6% in the good category, and on the 600-meter run endurance component with an average score of 2.37, achieving a percentage of 46.6% in the good category.